2018
DOI: 10.1007/s40477-018-0313-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound shear wave to measure muscle stiffness in children with cerebral palsy

Abstract: Measuring muscle properties with SWE, a non-invasive and real-time technique, may integrate the physical exam. SWE may be a reliable clinical tool for diagnosis and longitudinal monitoring of muscle stiffness, as well as particularly suitable for grading and for assessing the response to treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
(35 reference statements)
1
28
0
1
Order By: Relevance
“…| 2020 | Proc3 | VOLUME 15 © 2020 University of Alicante structures; technical equipment, like ultrasound guidance, are able to provide anatomical, functional and biomechanical information about the architecture of several components of musculoskeletal systems, providing qualitative information about the characteristics of involved tissues (with techniques like the elastography) (Vola et al, 2018) .…”
Section: S750mentioning
confidence: 99%
“…| 2020 | Proc3 | VOLUME 15 © 2020 University of Alicante structures; technical equipment, like ultrasound guidance, are able to provide anatomical, functional and biomechanical information about the architecture of several components of musculoskeletal systems, providing qualitative information about the characteristics of involved tissues (with techniques like the elastography) (Vola et al, 2018) .…”
Section: S750mentioning
confidence: 99%
“…Knowing these mechanisms could be relevant to define the effect of physical activity (Jones & Rutherford, 1987) , rehabilitation process and physical agents on muscle tissue in normal and pathological conditions (B Corrado, Albano, et al, 2019) (Vola et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…US features of PF include a thickened (> 4 mm) and hypoechoic aponeurosis close to its calcaneal attachment (Elias et al, 2013). Shear wave elastography (SWE) allows quantitative assessment of the stiffness of the plantar fascia and can highlights the classic alterations of PF Schillizzi et al, 2020;Vola et al, 2018). Contrary to popular belief, recent studies have demonstrated no correlation between fascial thickness and degree of symptoms (Meyer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%